FKE highlights academic excellence in collaboration with Universitas Negeri Malang - Sihab, Norsabrina; Setumin, Samsul (Electrical Engineering Studies, 2026)
KOTA MALANG - The Faculty of Electrical Engineering (FKE) further strengthened its international collaborative network with Universitas Negeri Malang (UM), Indonesia, through academic engagement. Associate Professor Ir. Ts. Dr. Samsul Setumin was invited as a speaker at the International Workshop on “Data Science in Digital Finance and Actuarial Science,” held from 12 to 15 November 2025. The program was fully sponsored by the Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Malang (UM), Indonesia. During the program, Dr. Samsul delivered a talk titled “Introduction to Data Science” to students and staff. The session provided exposure to essential data science principles, including the data science lifecycle, analytical processes, machine learning for predictive modelling, and applications of regression and time-series forecasting within actuarial contexts. The workshop served as a platform for meaningful knowledge exchange aligned with current industry needs in digital finance and analytics.